THE NATURE OF THE RELATIONSHIP BETWEEN PROPAGANDA DISCOURSE AND POLITICAL DISCOURSE - Mahmoud Nafal, Nazhat (ALBAHITH ALALAMI, 2008)
The propaganda discourse is the most widely circulated in the media and communication studies, where the interest of scholars and researchers in this field has become clear in the analysis and interpretation of the content of this discourse, to identify the intentions, purposes and objectives of the communicator activity, which exceeded the borders of states in the heated atmosphere of rivalries and political conflicts that characterize The countries of the world as a whole and for many years.In particular, the economically and militarily developed countries (the Nordic capitalist countries) have exerted special efforts in the production of information and ideas, using advanced methods and means in all details of communication work, leading to clear successes in changing the behavior and attitudes of public opinion in general and the target audience opinion of the communication work in particular. This is based on a psychological and social study of all that surrounds the public. All of this, in order to bring about the desired change, where the focus on the activity of institutions and communication agencies on propaganda as a key variable in the success of the efforts made through organized campaigns, we can say that the results and impact is stronger than the results of military wars, so-called propaganda wars.